Effects of aerobic exercise training in animal models of hypertension. - Palma, Renata Kelly da; Malfitano, Christiane; Shimojo, Guilherme Lemos; Sanches, Iris Callado; Angelis, Kátia De (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Background: Hypertension is one of the leading causes of death due to stroke, heart attack and kidney failure. The understanding of the pathophysiological mechanisms involved in its development and maintenance is critical to potential therapeutic interventions. Thus, animal models of hypertension have been used in the study of this disease for many years. Objective: To investigated the effects of dynamic aerobic exercise training as a non- pharmacological approach for the management of hypertension in animal models. Method/Design: This study is a literature review conducted in the Medline database. Results: The results demonstrated that aerobic exercise training may reduce blood pressure in different rat models of hypertension. Conclusions: The dynamic aerobic exercise can reduced blood pressure in different animal models of hypertension by mechanisms that involving neurohumoral changes, reinforcing the important role of this approach in the treatment of hypertension and its associated disorders.